PIsolation and Characterization of Salt Tolerant Strains of Sinorltizobium meliloti - Raad Sultan; Fawaz Al-Safar (College of Education for Pure Sciences, 2007)
Twenty four strains of Sinorhizobium meliloti were isolated from root nodules of alfalfa plants. Host plants collected from different agroclimatic regions of Ninavah province-Iraq. Five strains, vis. FA7, FA8, FAlO, FAll and FA12 were found tolerant to 6% NaCI. All the five strains were able to grow on rhizobia! minimal medium. The five studied strains showed multiple antibiotic resistance. The more sufficient production in shoot group in alfalfa plants found when the plants inoculated with F A8 and FA 7 strains. pH changes in MSY solid medium study revealed that changes in pH towards acidity. Reduction in colony forming units (CFU) was observed under salt conditions in comparison with normal conditions. Production of cell surface molecules in these five strains , such as, P-(1 ----+ 3) glucans, cellulose fibrils and exopolysaccharides were also studied. Heat curing of Sym plasmids study revealed that at least one of the salt tolerant genes lays on Sym plasmids.